Pengaruh Pemahaman E-Commerce, Pemahaman Sistem Informasi Akuntansi, dan Motivasi Berwirausaha terhadap Minat Mahasiswa Berwirausaha (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Entrepreneurship focuses on the values, skills, and behaviors required for individuals to navigate life’s challenges and seize opportunities despite potential risks. Several key factors influence students' interest in becoming entrepreneurs, including their understanding of e-commerce, familiarity with accounting information systems, and entrepreneurial motivation. This research aims to provide empirical evidence on how these three aspects affect students' interest in entrepreneurship. The study was conducted at the Faculty of Economics and Business, Udayana University, targeting undergraduate accounting students from the 2021 and 2022 cohorts. A total of 234 participants were selected through a simple random sampling technique. The data were analyzed using multiple linear regression. The findings reveal that all three variables—e-commerce knowledge, accounting information systems understanding, and entrepreneurial motivation—have a significant positive influence on students’ entrepreneurial interest, consistent with the Theory of Planned Behavior (TPB). These findings may serve as a strategic reference for the university to cultivate entrepreneurial spirit, boost students’ interest in starting businesses, reduce unemployment among graduates, and encourage self-sufficiency among future alumni.